Reduced clearance of venlafaxine in a combined treatment with quetiapine - Paulzen, Michael; Gründer, Gerhard (Progress in neuro-psychopharmacology & biological psychiatry, 2018)
Venlafaxine and the atypical antipsychotic quetiapine are often administered concomitantly. Both drugs share several metabolic hepatic pathways. However, pharmacokinetic interactions between venlafaxine and quetiapine have not been studied yet. A therapeutic drug monitoring database containing serum concentrations of venlafaxine (VEN) and its active metabolite O-desmethylvenlafaxine (ODVEN) was analyzed. Two groups of patients were compared: venlafaxine monotherapy V0 (n=153) and co-medication with quetiapine, VQUE (n=71). Serum concentrations of VEN, ODVEN, and active moiety, AM (VEN+ODVEN), metabolite to parent compound ratio (ODVEN/VEN) and dose adjusted serum concentrations were compared using non-parametrical tests without information on CYP2D6 genotype. The two groups did not differ in terms of the daily dosage of venlafaxine, age, or sex. Median serum concentrations in the quetiapine group showed significantly, 15.8% and 29.3% higher values for AM and ODVEN (p=0.002, Cohen's d=0,41; p=0.003, d=0,44), respectively. Dose adjusted serum concentrations of active moiety and ODVEN revealed comparable differences (p=0.038, d=0,32; p=0.015, d=0,28) with significantly higher values in the co-medicated group. Significantly higher values for ODVEN and AM suggest a reduced clearance of ODVEN and active moiety when quetiapine is co-administered. This may be a consequence of a reduced metabolism of venlafaxine to the inactive metabolite N-desmethylvenlafaxine via CYP3A4, the main metabolizing enzyme for quetiapine, and a shift towards a higher proportion of the active metabolite ODVEN. Therapeutic drug monitoring is recommended in the case of co-medication to ensure clinical efficacy and patient safety. Although the increase of AM is moderate, we consider it relevant for clinicians given the prevalence of concomitant medication of quetiapine and venlafaxine.